REHABILITATION OF DEVASTATED PEAT LANDS AND ESTABLISHMENT OF SUSTAINABLE AGRO-SYSTEMS THROUGH BUFFER ZONE PLANNING IN CENTRAL KALIMANTAN - Osaki, Mitsuru; Wijaya, Hanny; Simbolon, Herwint (Research Center for Biology-Indonesian Institute of Sciences, 2000)
-